Venture Capital - Success Factor for Business Ideas - K. B, Subhash (Ushus Journal of Business Management, 2021)
This article tries to give a comprehensive meaning to the concept of venture capital by taking into account all relevant aspects associated with it. Secondly the origin, growth and development of modern concept of venture capital around the world are being discussed. Thirdly, the present status of venture capital scenario explains about the trends and tendencies happening around the world. Finally the role of venture capital in promoting the economic development, a brief discussion on the impact of venture capital on the economy and the article concludes with the future trend.